PENGARUH SALURAN DISTRIBUSI TERHADA VOLUME PENJUALAN TELUR AYAM RAS DI PETERNAKAN WIJAYA KUSUMA FARM DESA MEGULUNG KIDUL KECAMATAN PITURUH KABUPATEN PURWOREJO (Prospect : Jurnal Manajemen dan Akuntansi, 2021)
This research aims to analyze "The Influence of Distribution Channels on the Sales Volume of Purebred Chicken Eggs from Wijaya Kusuma Farm, Megulung Kidul Village, Pituruh District, Purworejo Regency". This research uses data collection and survey techniques using questionnaires and literature study. The sample used purposive sampling technique. The variables related to this research are distribution channels on sales volume using a simple linear regression analysis method. All statements were tested using validity and reliability tests which had a correlation > 0.300 (valid) and had an alpha coefficient > 6.0 (reliable). Based on a simple correlation, it shows that the relationship between the distribution channel variable and the sales volume variable is 0.591, meaning that the distribution channel variable has a moderate relationship with the sales volume variable. The simple regression equation Y = 16.078+ 0.341X results in a constant of 16.078. Analysis of the coefficient of determination shows that the contribution results from distribution channel variables are 15.3% and 84.7% are influenced by other factors. The t test shows that H1 the distribution channel variable partially has a positive and significant influence on the sales volume variable. This is indicated by thitung being greater than ttabel(2.787 > 2.016) and a significant level of (0.008 < 0.05).